A novel method for assessing the role of iron and its functional chelation in fibrin fibril formation: the use of scanning electron microscopy. (June 2013) - Pretorius, Etheresia; Vermeulen, Natasha; Bester, Janette; Lipinski, Boguslaw; Kell, Douglas B.
Abstract Aims: Inflammatory diseases associated with iron overload are characterized by a changed coagulation profile, where there is a persistent presence of fibrin-like material of dense-matted deposits (DMDs). It is believed that one source of such material is a result of the activation of blood coagulation without the generation of thrombin, causing clots to become resistant to fibrinolytic dissolution. The aim of the current manuscript therefore is to apply a novel scanning electron microscopy method for assessing the role of functional chelation in the prevention or reversal of iron-induced fibrin formation. Methods and results: Purified fibrinogen and platelet-rich plasma were exposed to chelating agents followed by iron, to determine the chelating effects. We show that there is another, pathological pathway of fibrin formation initiated by free iron (initially as Fe (III)), leading to the formation of highly reactive oxygen species such as the hydroxyl radical that can oxidize and insolubilize proteins, a process that might be inhibited by iron-chelating compounds. The final product of such a pathway is a fibrin-like material, termed DMDs that are remarkably resistant to proteolytic degradation. Conclusions: Scanning electron microscopy shows that iron-chelating agents are effective inhibitors of DMD formation. The most active inhibitors of DMD formation proved to be Desferal, Clioquinol and Curcumin, whereas Epigallocatechin gallate and Deferiprone were less effective. The functional model we describe may point the clinical utility of various substances in iron-mediated degenerative diseases.